Xylaria sp.; Jamur Lilin dari Jawa Barat - Rudy Hermawan; Yuyun Nisaul Khairillah (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2021)
Candle snuff fungus belongs to Xylaria group. Generally, Xylaria has a form like stick or candle or elongated fruit of shapes. Xylaria is classified into Ascomycota within Xylariaceae. This study found one species of candle-shaped mushroom in IPB Unversity. This study aimed to identified and characterized the specimen using molecular and morphological data. The specimen was collected and preservedinto FAA solution and deposited into Herbarium Bogoriense as BO 24426. Molecular analyses using Large Subunit as a region for amplification showed that the BO 24426 was classified into Xylaria sp. This species closes to Xylaria consociata. The stromata were erected, unbranched, and tapered to the apex. The texture was rigid and hard. Ascus bore 8 ascospores. The ascospores were fusiform or bean-shaped and smooth. The morphological observations supported molecular identification of BO 24426 as Xylaria sp. Other genes were needed to ensure the exact species of Xylaria